Radiology Technologists Performing Peritoneal Drainage, Local Experience - I Aljediea; M Alshehri; K Alenazi; A Memesh; M Fleet (The Arab Journal of Interventional Radiology, 2022)
Purpose We conducted this study to review our experience of peritoneal drainages (paracentesis) performed by interventional radiology technologists. Materials and Methods This is a retrospective study of peritoneal drainages performed by interventional radiology technologists. Results We reviewed all peritoneal drainages performed in interventional radiology between November 2018 and November 2021. The review process included success rate, volume drained, catheter duration, and complications. Conclusion Interventional radiology technologists can safely perform ultrasound-guided peritoneal drainages. Extending Interventional radiology technologists' role to perform ultrasound-guided peritoneal drainages allows interventional radiologists to do more complex procedures, enhances the workflow, and increases the efficiency of the interventional radiology team.